Case Report: Can Inhaled Adenosine Attenuate COVID-19? - Spiess, Bruce D.; Sitkovsky, Michael; Correale, Pierpaolo; Gravenstein, Nikolaus; Garvan, Cynthia; Morey, Timothy E.; Fahy, Brenda G.; Hendeles, Leslie; Pliura, Thomas J.; Martin, Thomas D.; Wu, Velyn; Astrom, Corey; et al. (Frontiers in Pharmacology, 2021)
This case report demonstrates a small repetition of the case series carried out in Italy wherein inhaled adenosine was administered to patients experiencing severe and worsening coronavirus disease-2019 (COVID-19). The two cases are important not only because they were the first of their type in the United States, but also because both patients were DNR/DNI and were therefore expected to die. Study repetition is vitally important in medicine. New work in pharmacology hypothesizes that adenosine-regulator proteins may play a role in the pathogenesis of COVID-19 infection. Furthermore, adenosine, by interacting with cell receptor sites, has pluripotent effects upon inflammatory cells, is anti-inflammatory, and is important in tissue hypoxia signaling. Inhaled adenosine is potentially safe; thousands have received it for asthmatic challenge testing. The effects of adenosine in these two cases were rapid, positive, and fit the pharmacologic hypotheses (as seen in prior work in this journal) and support its role as a therapeutic nucleoside.